THE TELEWORK, A FLEXIBLE WAY TO WORK IN A CHANGING WORKPLACE - Victoria-Mihaela BRINZEA; Carmen-Gabriela SECARA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
When asked about the working hours, most Romanians will respond: five days a week, 8 hours a day, between 8:00 and 16:00 or between 9:00 and 17:00. But, worldwide, more and more companies choose to modify this traditional work program. The flexible work schedules appear as a reliable alternative, which, with the help of advanced technologies, eliminates the spatial barriers imposed by the traditional manner of work. The aim of our paper is to approach the telework as a version of the flexible program of work. To achieve this purpose, we have made a literature review to see how the telework is used nowadays in organizations. In this approach, we started from the conceptual definition of this term. We continued with the presentation of the implementation state of this manner of work in different countries and with the study of the factors that transform the telework into a widely-agreed way of working. Following the analysis, a number of advantages and limits of using the telework have been revealed, leading to the conclusion that, when it used correctly and consistently, this manner of flexible working meets the needs of the employees, but also of the employers, both actors being considered winners.